2001
DOI: 10.1007/978-3-662-08302-4
|View full text |Cite
|
Sign up to set email alerts
|

Lehrbuch der Lebensmittelchemie

Abstract: Dieses Werk ist urheberrechtlich geschiitzt. Die dadurch begriindeten Rechte, insbesondere die der Ubersetzung, des Nachdrucks, des Vortrags, der Entnahme von Abbildungen und TabeUen, der Funksendung, der Mikroverfilmung oder Vervielfaltigung auf anderen Wegen und der Speicherung in Datenverarbeitungsanlagen, bleiben, auch bei nur auszugsweiser Verwertung, vorbehalten. Eine Vervielfaltigung dieses Werkes oder von Teilen dieses Werkes ist auch im Einzelfall nur in den Grenzen der gesetzlichen Bestimrnungen des … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
306
0
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(330 citation statements)
references
References 0 publications
7
306
0
17
Order By: Relevance
“…The cleavage occurs from inside of the molecules. Amylose is split into oligosaccharides of 6-7 glucose units, whereas amylopectin is cleaved nonspecifically, leaving out the 1,6-α-branching points 6 . Ungermi- 51 , an increase in α-amylase activity has been reported during germination.…”
Section: Resultsmentioning
confidence: 99%
“…The cleavage occurs from inside of the molecules. Amylose is split into oligosaccharides of 6-7 glucose units, whereas amylopectin is cleaved nonspecifically, leaving out the 1,6-α-branching points 6 . Ungermi- 51 , an increase in α-amylase activity has been reported during germination.…”
Section: Resultsmentioning
confidence: 99%
“…Green tea is known to have a high content of polyphenolic substances up to about 25-30% of its dry weight ( Fig. 3; Belitz and Grosch 1992;Koolman et al 2003). We also had some evidence from former experiments with fruit peel extracts which showed that these substances should have a positive effect on O. oeni.…”
Section: Resultsmentioning
confidence: 99%
“…4.40-6.50 mg · 100 g -1 (Fineli, 2011), 7.00 mg · 100 g -1 (Frede, 2006) and 8.00 mg · 100 g -1 (Belitz, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%